Reflections on the divine grace from the new testament - Condori Cutimbo, Claudio Raúl (Universidad Femenina del Sagrado Corazón, 2017)
This essay reflects the Grace from a theology perspective in order to raise awareness about its importance in the Christian’s life and discover that God is always helping us with his Grace. Its understanding is addressed in the Old Testament, where it does not appear explicitly the concept of Grace, but there are elements that allow us to recognize it as Divine Grace, especially the covenant that God established with his chosen people. In the New Testament this understandingis specified from the very preaching and action of Jesus. All this way leads us to recognize that God from his infinite love continues helping us with his Grace, but always respecting our freedom, even in moments when we feel that God seems to be absent from our lives.